The Effect of the TGT Learning Model Assisted by One-Sided Flashcards on the Cognitive Domain Assessment Results of Seventh Grade Students in Fiqh at MTs Sumbersari Kowang - Hasanah, Rofi’atul; Ana Achoita (The Future of Education Journal, 2025)
The purpose of this study was to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model, supported by One-Sided Flashcards, on students' cognitive domain assessment results in the seventh-grade Islamic Jurisprudence (Fiqh) subject. The background of this study stems from the low level of active student participation in the learning process, which tends to be one-way and lacks variety. Using a quantitative approach, this study employed a One Group Pretest-Posttest Design. The subjects consisted of seventh-grade students at MTs Sumbersari Kowang, with data collection techniques including questionnaires, tests, and documentation. Data analysis was conducted using t-tests and Pearson correlations. The results showed a significant improvement in cognitive assessment results after implementing the One-Sided Flashcard-assisted TGT model, with a significance value of <0.001. The Pearson correlation of 0.0471 indicates a fairly strong relationship, and the effect size of 2.85 indicates a high influence. Thus, the use of the TGT model, supported by visual media, has proven effective in supporting students' cognitive learning outcomes in Fiqh.